Alopecia Areata: Impact on Patients’ Quality of Life and Disease Perception: A Survey-Based Study - Christian Vestergaard; Daniel de la Rosa Carrillo; Randeep Mandla; Anne Grete Frøstrup; Susanne T. Gren; Petri Vänni; Anna-Kaisa Asikainen; Kristian Kofoed; Cato Mørk (Acta Dermato-Venereologica, 2025)
Alopecia areata significantly impacts patients’ emotional and psychosocial well-being. This survey investigated patients’ perspectives on disease severity and its impact on quality of life. The study evaluated whether disease assessment tools (Severity of Alopecia Tool, Dermatology Life Quality Index, and Patient Unique Stigmatization Holistic tool in dermatology) reflect patients’ perceptions of their condition. The study was conducted as an anonymous social media survey in Norway and Denmark. The questionnaire was divided into 3 main sections: (i) demographics and disease characteristics; (ii) disease severity and QoL measures; and (iii) patient perception and psychosocial impact. A total of 360 individuals participated in the survey reporting alopecia areata as mild (15%), moderate (29%), or severe (58%). Some 61% reported alopecia areata to interfere with their daily or weekly activities. All disease assessment tools demonstrated an age-dependent pattern, where scores were highest in the youngest (< 30 years) responder group. The relationship between Dermatology Life Quality Index and Severity of Alopecia Tool scores was found to be weak (R-squared = 0.08). Similarly, the correlation between Dermatology Life Quality Index and self-reported disease severity was also weak (R-squared = 0.136). This study demonstrates that there is a clear need for the development of more comprehensive, validated, and patient-centred assessment tools that can accurately reflect the physical, emotional, psychological, and social challenges faced by individuals with alopecia areata.